answersLogoWhite

0


Best Answer

c=a-b

User Avatar

Angel Alejandre

Lvl 4
βˆ™ 3y ago
This answer is:
User Avatar
More answers
User Avatar

Wiki User

βˆ™ 10y ago

1+8/c=5/3

This answer is:
User Avatar

Add your answer:

Earn +20 pts
Q: Rewrite the formula to solve for c?
Write your answer...
Submit
Still have questions?
magnify glass
imp
Continue Learning about Geometry

How do you find the diameter of a cylinder if the volume is 615.8 and the height is 4?

The formula for the volume of a cylinder is V = 2 * pi * r * h, where r is the radius, h is the height, and pi is 3.14159... Since the diameter is twice the radius, rewrite the formula as V = pi * d * h, solve for d, plug in your values, and compute.


How do you find the degree of a not-right angled triangle with only two side lengths and the area of that triangle?

the angle between the two sides is used in the formula A = 1/2 a*b*sin(C) where A is area, a and b are side lengths, and C is the angle between sides. Simply use algebra to rearrange the formula to solve for C.


Formula of radious given curve length and chord length?

R = radius c = chord length s = curve length c = 2Rsin(s/2R) you can solve for radius by trial and error as this is a transcendental equation


Find the circumference of a circle of 10 cm using 3.14?

I am assuming the 10cm is the diameter. C/d = pi, where C is circumference, d is the diameter, and pi is 3.14159. To find circumference, we change the formula to solve for C. C = pi x d = 3.14159 x 10cm = 31.4159cm


What is the radius of a circle of a circumference of 121?

To find the radius of a circle with a circumference of 121, you can use the formula for the circumference of a circle: C = 2Ο€r, where C is the circumference and r is the radius. Given that the circumference is 121, you can plug this value into the formula and solve for the radius. Dividing 121 by 2Ο€ will give you the radius of the circle, which is approximately 19.24 units.

Related questions

Rewrite the formula to solve for the length?

l= A/ W


A equals 2bc - d how do you rewrite the original formula to solve for c?

A = 2bc - dAdd 'd' to each side of the equation:A + d = 2bcDivide each side by 2b :(A + d)/2b = c


Which formula for a 2b c is correctly rewritten from the original formula to solve for c?

None.


Newton's Second Law of Motion uses the formula which states that a force will cause a mass to accelerate. (f = m β€’ a)Rewrite the formula to solve for a?

a=f/ m


Newton's Second Law of Motion uses the formula which states that a force will cause a mass to accelerate. (f = m β€’ a)Rewrite the formula to solve for m?

m= f/a


For a equals 2b plus c what is the correct formula rewritten from the original formula to solve c?

a = 2b + c then a - 2b = c ie c = a - 2b


How can you rewrite a3b-2c to solve for b?

5


What is the formula to solve for b a equals 2b plus c?

If: a = 2b+c Then: a-c = 2b And: b = (a-c)/2


Which of these formulas is correctly rewritten from the original formula to solve for c a equals 2b plus c?

c= a-2b


A equals 2b plus c Which of these formulas is correctly rewritten from the original formula to solve for c?

a-2b=c


What is the formula to solve constant function?

The answer depends on what information you already have. The simplest version of a formula is f(x) = c.


Which of these formulas is correctly rewritten from the original formula to solve for c?

a=2 BC - d is c=2(a + b)